DNA-Sensing Antiviral Innate Immunity in Poxvirus Infection - Lu, Yue; Zhang, Leiliang (Frontiers in Immunology, 2020)
As pattern recognition receptors, cytosolic DNA sensors quickly induce an effective innate immune response. Poxvirus, a large DNA virus, is capable of evading the host antiviral innate immune response. In this review, we summarize the latest studies on how poxvirus is sensed by the host innate immune system and how poxvirus-encoded proteins antagonize DNA sensors. A comprehensive understanding of the interplay between poxvirus and DNA-sensing antiviral immune responses of the host will contribute to the development of new antiviral therapies and vaccines in the future.